Systems thinking, archetypes, and management: an exploratory study - Fontaine, Rodrigue Ancelot Harvey (World Academy of Islamic Management, 2023)
As time goes by, organizations are becoming more and more complex. One tool that can be used to make sense of this complexity is systems thinking. In particular, Herasymowych and Senko (2007) suggested that there are negative and positive systems archetypes in every management situation. If managers learn to use these archetypes, it will help them make better decisions. In this light, this study explores how a group of MBA students responded to positive and negative systems archetypes. The study concludes that such knowledge will help Muslim managers in the future.